Analisis Sistem Antrian Menggunakan Metode Discrete Event Simulation pada Coffee Shop di Kota Cilegon - Mohamad Jihan Shofa; Ahmad Rifai Lubis; Akbar Utama Prastyo; Rifky Aditiya; Muhamad Rizki Dermawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Coffee Shop di Kota Cilegon faces queuing system issues due to high customer arrival rates during peak operating hours, while the ordering process is handled by only one cashier. This situation leads to increased wait times and reduced service efficiency. This study aims to evaluate the performance of the queuing system and determine the most optimal improvement alternatives using the Discrete Event Simulation (DES) method with the assistance of Arena software. Research data were obtained through observations of 100 customers and then analyzed using the Input Analyzer to determine the inter-arrival time distribution and service time. Simulation results show that under current conditions, the average wait time is 1,910.85 seconds with a cashier utilization rate of 100%, meaning that service capacity is unable to keep pace with customer arrival rates. Improvement alternatives, such as adding cashiers and self-ordering kiosks, were found to make a significant difference (Sig. < 0.001). Based on the simulation results, self-ordering kiosks resulted in the lowest waiting time and are therefore recommended as the best solution for improving queue system efficiency and service quality.